(untitled) (Journal of Applied Learning and Teaching, 2019)
The paper looks into the current situations of the four Asian language programs, including Chinese, Japanese, Korean, and Vietnamese, at the University of Georgia in the fall of 2018, in order to point out similar issues among them as well as different problems particular to some of them. Reflecting the local, national, and international circumstances, the findings largely, but not entirely, confirm the recent data provided by the Modern Language Association and the United States Census Bureau. Possible solutions to the issues include the hiring of non-native graduate teaching assistants as language teachers, the creation and expansion of exchange programs, and more effective utilization of funding for recruitment.